1989
DOI: 10.1152/jn.1989.61.5.900
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of neuronal firing correlation: modulation of "effective connectivity"

Abstract: SUMMARYAND CONCLUSIONS 1. We reexamine the possibilities for analyzing and interpreting the time course of correlation in spike trains simultaneously and separably recorded from two neurons.2. We develop procedures to quantify and properly normalize the classical joint peristimulus time scatter diagram. These allow separation of the "raw" correlation into components caused by direct stimulus modulations of the single-neuron firing rates and those caused by various types of interaction between the two neurons.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
767
1
4

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,014 publications
(796 citation statements)
references
References 20 publications
(3 reference statements)
8
767
1
4
Order By: Relevance
“…A very useful graphical display for this purpose is the joint poststimulus time histogram (JPSTH; Aertsen et al 1989). This extends the PSTH by counting the number of trials on which spikes occur for both neuron 1 at time u and neuron 2 at time v, with the aim of indicating the times (and relative time lags v Ϫ u) at which large numbers of joint spikes occur.…”
Section: The Tendency Of Two Neurons To Act Together May Be Displayedmentioning
confidence: 99%
“…A very useful graphical display for this purpose is the joint poststimulus time histogram (JPSTH; Aertsen et al 1989). This extends the PSTH by counting the number of trials on which spikes occur for both neuron 1 at time u and neuron 2 at time v, with the aim of indicating the times (and relative time lags v Ϫ u) at which large numbers of joint spikes occur.…”
Section: The Tendency Of Two Neurons To Act Together May Be Displayedmentioning
confidence: 99%
“…One approach to understanding the dynamic nature of connections between local and distant neural assemblies is the analysis of functional and effective connectivity (Friston et al, 1994): the former captures patterns of statistical dependence, whereas the latter attempts to extract networks of causal influences of one physiological time series over another (Aertsen et al, 1989). Several studies have demonstrated changes in functional connectivity patterns after brain tumor resection (Douw et al, 2008), recovery from stroke (Gerloff et al, 2006), and traumatic brain injury (Castellanos et al, 2010;Zouridakis et al, 2012), suggesting that functional connectivity graphs (FCGs) of brain activity are sensitive to changes due to brain insult.…”
Section: Introductionmentioning
confidence: 99%
“…A particularly important application in this respect concerns their use as control measurements against which to test multiple single-unit spike data for the presence of dynamic spike synchronization phenomena (Gerstein and Aertsen, 1985;Aertsen et al, 1987Aertsen et al, , 1989Riehle et al, 1997;Grü n et al, 1999).…”
Section: Discussionmentioning
confidence: 99%